Telegrama de R. V. Pérez Merchand a Emilio S. Belaval. - Perez Machado, R V (My University, 1962)
Telegrama relacionado a felicitaciones por su obra.
Keywords: Perez Marchand, R. V.--Correspondence.; Perez Marchand, R. V.--Correspondencia.; Belaval Maldonado, Emilio S.--Correspondence.; Belaval Maldonado, Emilio S.--Correspondencia.